Modeling the role of information on the spread of online shopping. Issue 5 (22nd July 2021) - Sharma, Sandeep
Abstract: For at least the past 5 years, online shopping has witnessed exponential growth. The trend of online shopping is very much popular in current times. In particular, the young population frequently turned up to different online shopping sites for their routine purchase. The information or awareness created by online shoppers also plays a pivotal role in the growth of online shopping. People got attracted to online shopping when they heard about attractive offers, discounts, and other benefits of online shopping from someone on their social network. Moreover, online shopping sites also introduced the review and rating facilities for individual products listed on their web page or mobile applications. Online buyers also use the information provided by the reviews before finalizing the purchase of an item. Motivated by these facts, in this article, we propose a compartmental mathematical model to study the impact of information on the growth of online shopping. The model subsequently subjected to dynamical analysis using the tools of dynamical systems and the theory of differential equations. Numerical simulation has been performed to validate our analytical findings.